GAP HARAPAN NASABAH DENGAN PERSEPSI MANAJEMEN ATAS KUALITAS LAYANAN - dimyati, mohamad (Universitas Jember, 2015)
Abstract. The purposes oh this research are to examine the existance of gap between the expectation of customesr and the perception of management on the service quality at the DSP Bank in Jember regency. The questionnaire was used as the research instrument. The service quality dimentions examined in this reseach are tangibles, reliability, reponsiveness, assurance, and emphaty. The population of this research is all customer DSP Bank and all employee DSP Bank in Jember regency. The total sample size was 120 respondents (99 are customer and 21 are employee). The models of analysis used in the research are gap analysis and Mann-Whitney test. The results of analysis show that the expectation of customer on the quality of service at the DSP Bank in Jember regency for the dimentions of tangibles and emphaty on average is higher than the perception management. Whereas for the dimentions of reliability, responsiveness, and assurance on average is lower higher than the perception management. The results of significancy test with Mann-Whitney test suggest that research hypothesis for the dimention of reliability, responsiveness and assurance in accepted. This means there is a gap between customer expectation and the management perception. Whereas research hypothesis for the domentions of tangibles and emphaty in rejected. This means there is not is a gap between customer expectation and the management perception. Key words: customer expectation on the service quality, management perception, dimentions of service quality